Evaluation of Fetuses Diagnosed with Megacystis During Prenatal Period - Sarsmaz, Kemal; Kanyildiz, Busra; Orgul, Gokcen; Karakoc, Gokhan; Eroglu, Hasan; Sahin, Dilek; Yucel, Aykan (Gynecology Obstetrics & Reproductive Medicine, 2021)
Objectives: Fetal megacystis is very rare; however this problem may be associated with other structural or chromosomal abnormalities leading to morbidity and mortality. Due to renal injury and pulmonary hypoplasia, prognosis is poor especially in fetuses with early onset oligohydramnios. In this study, we evaluated the management strategies and outcomes of fetal megacystis in our hospital. Study Design: The data of cases who were prenatally diagnosed with megacystis between 1 January 2017 and 31 December 2019 were analyzed. Ultrasonography findings and antennal interventions were withdrawn from computerized database. Information about postpartum status was also received. The data were analyzed in terms of diagnostic methods, fetal interventions (vesicosynthesis (VS), vesicoamniotic shunt (VAS)), potential prognostic markers and short/long-term prognostic results. Results: A total of 15 megacystis patients were detected. One of the fetuses was female and the remaining cases were male. Six of the patients were isolated. Ten patients underwent invasive procedures for prenatal aneuploidy diagnosis and one of them diagnosed with trisomy 18. Totally, 4 patients underwent VS; however no VAS was recorded. Four fetuses were terminated and intrauterine fetal demise occurred in 2 fetuses. Four patients were lost during follow up. Survival rate was 33.3%. Conclusion: Fetal megacystis is an important ultrasonographic finding which may be a component of chromosomal / genetic anomalies. This problem may also be isolated in some cases. Because of the poor outcome, parents should be well informed and all interventions should be offered to families.